2021
DOI: 10.1097/txd.0000000000001260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Steroid Withdrawal on Posttransplant Diabetes Among Kidney Transplant Recipients Differs by Recipient Age

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, this observation also raises important clinical questions such as to what extent the intensity of the immune suppressive drugs could be lowered, specifically in the long term. Such a question is important in elderly recipients with an aged immune system, who are prone to infectious, metabolic, and cardiovascular side effects of immune suppressive medication [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…However, this observation also raises important clinical questions such as to what extent the intensity of the immune suppressive drugs could be lowered, specifically in the long term. Such a question is important in elderly recipients with an aged immune system, who are prone to infectious, metabolic, and cardiovascular side effects of immune suppressive medication [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Early steroid withdrawal may have differential impact stratified by age, with older SOT recipients in a population-cohort study demonstrating more favourable responses to steroid withdrawal (e.g. lower PTDM and mortality) but increased risk for rejection [ 35 ]. Balancing PTDM versus graft-related concerns with steroid avoidance/withdrawal is essential, although patient/graft survival should take priority.…”
Section: Opinion Statement 5: Choose An Immunosuppression Regimen For...mentioning
confidence: 99%
“…For instance, early steroid withdrawal especially benefits older adults in terms of posttransplant diabetes mellitus prevention. Ahn et al have demonstrated in USRDS data in over 12,000 kidney transplant recipients that recipients over 55 years had a significantly higher benefit of steroid withdrawal than younger recipients (aHR for diabetes: 0.71 for >55 years vs. 1.18 in the age category 18–29 years) ( 107 ). Furthermore, a major competitive risk factor for graft loss in older adults is death with a functioning graft.…”
Section: Managing Maintenance Immune Suppression Regimens In Relation...mentioning
confidence: 99%